Pengaruh Karakter Individu, Sikap Mandiri, Dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha (Studi Kasus pada Siswa SMK Yadika 5 di Tangerang Selatan - Widi Wahyudi; Bella Safitri (Journal of Management and Creative Business, 2023)
This study aims to determine the significant effect of Individual Character, Independent Attitude, and Entrepreneurship Knowledge on Entrepreneurial Interest at SMK Yadika 5 in South Tangerang. The population in this study were students of SMK Yadika 5 in South Tangerang. Determination of the sample used in this study as many as 75 respondents using the Slovin formula approach technique. This retrieval uses a probability sampling technique. sampling using the analytical tool used is descriptive (primary data) by using a questionnaire spread yes using a Likert scale. The research analysis tool uses SPSS version 20 software. The results of multiple linear analysis using multiple linear regression analysis method Y = 14,542 + 0,597 (X1) - 0,228 (X2) + 0,401 (X3) + €. The conclusion in this study is that individual character, entrepreneurial knowledge has a significant effect on interest in entrepreneurship. Independent attitude has no significant effect on interest in entrepreneurship.